Hadith #2277 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; Ali ibn Abi Talib; Muhammad bin Ibrahim bin al-Harith محمد بن إبراهيم بن الحارث; Nafi' b. 'Ujayr b. 'Abd Yazid b. Hashim; Ujayr bin 'Abd Yazid bin Hashim; Yazid bin 'Abdullah bin Usama B. al-Haad يزيد بن عبد الله بن أسامة بن الهاد (Sunan Abi Dawud)
While I was sitting with AbuHurayrah, a Persian woman came to him along with a son of hers. She had been divorced by her husband and they both claimed him. She said: AbuHurayrah, speaking to him in Persian, my husband wishes to take my son away. AbuHurayrah said: Cast lots for him, saying it to her in a foreign language. Then her husband came and asked: Who is disputing with me about my son? AbuHurayrah said: O Allah, I do not say this, except that I heard a woman who came to the Messenger of Al
Grade: Sahih

Hadith #2279 - Sunan Abi Dawud - Aabad bin Musa al-Khtly عباد بن موسى الختلي; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Ali ibn Abi Talib; Isma'il bin Ja'far bin Abi Kathir إسماعيل بن جعفر بن أبي كثير الأنصاري; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق (Sunan Abi Dawud)
This tradition has been narrated by ‘Abd Al Rahman bin Abi Laila through a different chain of narrators. This version has “He decided that she would be given to Ja’far and said “Her maternal aunt is with him(i.e., his wife).
Grade: Sahih

Hadith #2564 - Sunan Abi Dawud - Abdullah bin Zryr عبد الله بن زرير; al-Laith bin Sa'd الليث بن سعد; Ali ibn Abi Talib; Marthad bin 'Abdullah al-Yazni مرثد بن عبد الله اليزني; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Yazid bin Abi Habib يزيد بن أبي حبيب (Sunan Abi Dawud)
Jabir reported the Prophet (ﷺ) as saying when an ass which had been branded on its face passed him. Did it not reach you that I cursed him who branded the animals on their faces or struck them on their faces. So he prohibited it.
Grade: Sahih

Hadith #2624 - Sunan Abi Dawud - Abu 'Abdur Rahman al-Salmi أبو عبد الرحمن السلمي; Ali ibn Abi Talib; Amr bin Marzuq al-Bahli عمرو بن مرزوق الباهلي; Sa'd bin 'Ubaida al-Salmi سعد بن عبيدة السلمي أبو حمزة; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Zubayd bin al-Harith زبيد بن الحارث اليامي (Sunan Abi Dawud)
Ibn Juraij said “O ye who believe, Obey Allaah and obey the Apostle and those charged with authority amongst you.” This verse was revealed about ‘Abd Allaah bin Qais bin ‘Adi whom the Prophet (ﷺ) sent along with a detachment. Ya’la narrated it to me from Sa’id bin Jubair on the authority of Ibn ‘Abbas.
Grade: Sahih

Hadith #2664 - Sunan Abi Dawud - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Ali ibn Abi Talib; Harithh bin Mdrb حارثة بن مضرب; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Uthman bin 'Umar bin Fars عثمان بن عمر بن فارس (Sunan Abi Dawud)
The Prophet (ﷺ) said at the battle of Badr: When they come near you shoot arrows at them; and do not draw swords at them until they come near you.
Grade: Da'if

Hadith #2695 - Sunan Abi Dawud - Abdul Salam bin Harb bin Salm al-Mala'i عبد السلام بن حرب بن سلم النهدي الملائي; al-Hakam bin 'Utayba الحكم بن عتيبة; Ali ibn Abi Talib; Ishaq bin Mansur al-Kausaj إسحاق بن منصور بن بهرام - الكوسج; Maymun bin Abi Shbyb ميمون بن أبي شبيب; Uthman bin Muhammad (Sunan Abi Dawud)
Abu Talhah said “When the Apostle of Allaah(ﷺ) prevailed on any people, he stayed three nights in the field. Ibn Al Muthanna said “When he prevailed over people, he liked to stay three nights in the field.” Abu Dawud said “Yahya bin Sa’id used to object to this tradition for this is not from his early traditions because his memory was spoiled at the age of forty five. He narrated this tradition in the last days of his age.” Abu Dawud said “ It is said that Waki ‘ recived this t
Grade: Sahih

Hadith #2699 - Sunan Abi Dawud - Aban bin Salah bin 'Umayr أبان بن صالح بن عمير; Abdul 'Aziz bin Yahya bin Yusuf عبد العزيز بن يحيى بن يوسف البكائي; Ali ibn Abi Talib; Ibn Ishaq محمد بن إسحاق بن يسار‎; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Muhammad bin Salmah محمد بن سلمة بن عبد الله الباهلي; Raba'i bin Harash bin Jahsh ربعي بن حراش (Sunan Abi Dawud)
Nafi said that a horse of Ibn ‘Umar went away and the enemy seized it. The Muslims overpowered them. Khalid bin Walid returned it to him after the Prophet (ﷺ).
Grade: Sahih

Hadith #2803 - Sunan Abi Dawud - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Ali ibn Abi Talib; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
I came to Utbah ibn AbdusSulami and said: AbulWalid, I went out seeking sacrificial animals. I did not find anything which attracted me except an animal whose teeth have fallen. So I abominated it. What do you say (about it)? He said: Why did you not bring it to me? He said: Glory be to Allah: Is if lawful for you and not lawful for me? He said: Yes, you doubt and I do not doubt. The Messenger of Allah (ﷺ) has forbidden an animal whose ear has been uprooted so much so that its hole appears (ou
Grade: Da'if

Hadith #2804 - Sunan Abi Dawud - Ali ibn Abi Talib; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Qatada قتادة (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) enjoined upon us to pay great attention to the eye and both ears, and not to sacrifice a one-eyed animal, and an animal with a slit which leaves something hanging at the front or back of the ear, or with a lengthwise slit with a perforation in the ear. I asked AbuIshaq: Did he mention an animal with broken horns and uprooted ears? He said: No. I said: ‘What is the Muqabalah ?’ He replied: ‘It has been cut from the back of its ear.’ I said: ‘What about the S
Grade: Da'if

Hadith #2982 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; Abu Ja'far al-Razi أبو جعفر الرازي; Ali ibn Abi Talib; Matruf bin Tarayf al-Harithi مطرف بن طريف; Yahya bin Abi Bkyr يحيى بن أبي بكير واسمه نسر (Sunan Abi Dawud)
Yazid ibn Hurmuz said that when Najdah al-Haruri performed hajj during the rule of Ibn az-Zubayr, he sent someone to Ibn Abbas to ask him about the portion of the relatives (in the fifth). He asked: For whom do you think? Ibn Abbas replied: For the relatives of the Messenger of Allah (ﷺ). The Messenger of Allah (ﷺ) divided it among them. Umar presented it to us but we found it less than our right. We, therefore returned it to him and refused to accept it.
Grade: Sahih

Hadith #2985 - Sunan Abi Dawud - Ahmed bin Salah al-Masri أحمد بن صالح المصري; al-Husain bin 'Ali bin al-Walid al-Ja'fi الحسين بن علي بن الوليد الجعفي; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Ali ibn Abi Talib; Anbs'h bin Khalid bin Yazid عنبسة بن خالد بن يزيد; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
AbdulMuttalib ibn Rabi’ah ibn al-Harith said that his father, Rabi’ah ibn al-Harith, and Abbas ibn al-Muttalib said to AbdulMuttalib ibn Rabi’ah and al-Fadl ibn Abbas: Go to the Messenger of Allah (ﷺ) and tell him: Messenger of Allah, we are now of age as you see, and we wish to marry. Messenger of Allah, you are the kindest of the people and the most skilled in matchmaking. Our fathers have nothing with which to pay our dower. So appoint us collector of sadaqah (zakat), Messenger of All
Grade: Sahih

Hadith #2987 - Sunan Abi Dawud - Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; Ali ibn Abi Talib; Sa'id bin Iyas al-Jariri سعيد بن إياس الجريري; Yahya bin Khlf al-Bahly يحيى بن خلف الباهلي أبو سلمة البصري (Sunan Abi Dawud)
Umm Al Hakam or Duba’ah daughters of Al Zibair bin ‘Abd Al Muttalib said “Some captives of war were brought to the Apostle of Allaah(ﷺ). I and my sister Fatimah, daughter of Apostle of Allaah(ﷺ) went (to the Prophet) and complained to him about our existing condition. We asked him to order (to give) us some captives. The Apostle of Allaah(ﷺ) said “the orphans of the people who were killed in the battle of Badr came before you (and they asked for the captives). But I tell you someth
Grade: Sahih

Hadith #3097 - Sunan Abi Dawud - Abdullah bin Nafi' al-Sa'agh عبد الله بن نافع الصائغ المخزومي; al-Hakam bin 'Utayba الحكم بن عتيبة; Ali ibn Abi Talib; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone performs ablution well and pays a visit to his (sick) Muslim brother seeking his reward from Allah, he will be removed a distance of seventy years (kharif) from Hell. I asked: What is kharif, Abu Hamzah? He replied: A year. Abu Dawud said: Only the people of Basrah have narrated the tradition on visiting the sick after performing ablution.
Grade: Da'if

Hadith #3098 - Sunan Abi Dawud - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; al-Hakam bin 'Utayba الحكم بن عتيبة; Ali ibn Abi Talib; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Uthman bin Muhammad (Sunan Abi Dawud)
If a man visits a patient in the evening, seventy thousand angels come along with him seeking forgiveness from Allah for him till the morning, and he will have a garden in the Paradise.
Grade: Da'if

Hadith #3099 - Sunan Abi Dawud - al-Hakam bin 'Utayba الحكم بن عتيبة; Ali ibn Abi Talib; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Uthman bin Muhammad (Sunan Abi Dawud)
This tradition has been narrated by Mansur from al-Hakkam as narrated by Shu’bah.
Grade: Sahih

Hadith #3139 - Sunan Abi Dawud - Ali bin Sahl bin Qadim علي بن سهل بن قادم; Ali ibn Abi Talib; Asim bin Dmrh al-Slwly عاصم بن ضمرة السلولي الكوفي; Habib bin Abi Thabit حبيب بن أبي ثابت قيس; Hajjaj bin al-Minhal حجاج بن المنهال; Ibn Jurayj ابن جريج (Sunan Abi Dawud)
He combined two persons from among the martyrs of Uhud in one garment.
Grade: Sahih

Hadith #3153 - Sunan Abi Dawud - Ali ibn Abi Talib; Amir al-Sha'bi عامر الشعبي; Isma'il bin Abi Khalid al-Ahmsi إسماعيل بن أبي خالد الأحمسي; Muhammad bin 'Ubaid bin Muhammad محمد بن عبيد بن محمد بن واقد (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) was shrouded in three garments made in Najran: two garments and one shirt in which he died. Abu Dawud said: The narrator ‘Uthman said: In three garments: two red garments and a shirt in which he died.
Grade: Da'if

Hadith #3174 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Ali ibn Abi Talib; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Nafi' bin Jubayr bin Mut'im نافع بن جبير بن مطعم; Yahya bin Sa'id al-Ansari يحيى بن سعيد الأنصاري (Sunan Abi Dawud)
We were with the Prophet (ﷺ) when a funeral passed hi and he stood up for it. When we went to carry it, we found that it was a funeral of a Jew. We, therefore said: Messenger of Allah, this is the funeral of a Jew. He said: Death is fearful event, so when you see a funeral, stand up.
Grade: Sahih

Hadith #3381 - Sunan Abi Dawud - Ali ibn Abi Talib; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Ibn Sirin محمد بن سيرين الأنصاري; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان (Sunan Abi Dawud)
Habal al-habalah means that a she-camel delivers an offspring and then the offspring which it delivers becomes pregnant.
Grade: Sahih

Hadith #4014 - Sunan Abi Dawud - Ali bin Sahl bin Qadim علي بن سهل بن قادم; Ali ibn Abi Talib; Asim bin Dmrh al-Slwly عاصم بن ضمرة السلولي الكوفي; Habib bin Abi Thabit حبيب بن أبي ثابت قيس; Hajjaj bin al-Minhal حجاج بن المنهال; Ibn Jurayj ابن جريج (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) sat with us and my thigh was uncovered. He said: Do you not know that thigh is a private part ?
Grade: Sahih

Hadith #4042 - Sunan Abi Dawud - Abu Salah Maula 'Uthman أبو صالح مولى عثمان; Ali ibn Abi Talib; Muhammad bin 'Ubaidullah bin Sa'id محمد بن عبيد الله بن سعيد أبو عون الثقفي; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Sulaiman bin Harb سليمان بن حرب (Sunan Abi Dawud)
‘Umar wrote to ‘Utbah b. Farqad that the Prophet (ﷺ) forbade (wearing) silk except so-and-so, and so-and-so, to the extent of two, three, or four fingers.
Grade: Sahih

Hadith #4043 - Sunan Abi Dawud - Abdullah bin Hnyn عبد الله بن حنين الهاشمي; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Ali ibn Abi Talib; Ibrahim bin 'Abdullah إبراهيم بن عبد الله بن حنين; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Nafie' نافع مولى ابن عمر (Sunan Abi Dawud)
A robe containing silk was presented to the Messenger of Allah (ﷺ). He then sent it to me. I wore it and came to him. I saw him looking angry in his face. He then said: I did not send it to you to wear. He ordered me and I divided it among my women.
Grade: Sahih

Hadith #4044 - Sunan Abi Dawud - Abdullah bin Hnyn عبد الله بن حنين الهاشمي; Abdur-Razzaq عبد الرزاق بن همام; Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ali ibn Abi Talib; Ibrahim bin 'Abdullah إبراهيم بن عبد الله بن حنين; Ma'mar bin Rashid معمر بن راشد (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) forbade us to wear a Qassi garment, a garment dyed with safflower, gold rings, and reading the Qur’an while bowing.
Grade: Sahih

Hadith #4049 - Sunan Abi Dawud - Ali ibn Abi Talib; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس; Ruh bin 'Ubada bin al-'Ala' روح بن عبادة بن العلاء; Ubaida bin 'Amr al-Salamani عبيدة بن عمرو; Yahya bin Habib bin Arby يحيى بن حبيب بن عربي (Sunan Abi Dawud)
my companion went to the mosque before me. I went there after him and sat beside him. He asked me: Did you hear the preaching of AbuRayhanah? I said: No. He said: I heard him say: The Messenger of Allah (ﷺ) forbade ten things: Sharpening the ends of the teeth, tattooing, plucking hair, men sleeping together without an under garment, women sleeping together without an under-garment, men putting silk at the hem of their garments like the Persians, or putting silk on their shoulders like the Pers
Grade: Da'if

Hadith #4050 - Sunan Abi Dawud - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Ali ibn Abi Talib; Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
It is forbidden to use purple saddle-clothes.
Grade: Sahih

Hadith #4056 - Sunan Abi Dawud - Abdullah bin Zryr عبد الله بن زرير; al-Laith bin Sa'd الليث بن سعد; Ali ibn Abi Talib; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Yazid bin Abi Habib يزيد بن أبي حبيب (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) gave license to ‘Abd al-Rahman b. ‘Awf and al-Zubair b. al-‘Awwam to wear silk shirts during a journey because of an itch which they had.
Grade: Sahih

Hadith #4151 - Sunan Abi Dawud - Abu Zara' bin 'Amr /Harm أبو زرعة بن عمرو/هرم; Ali bin Mdrk al-Nkh'y علي بن مدرك النخعي; Ali ibn Abi Talib; Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) never left in his house anything containing the figure of a cross without destroying it.
Grade: Sahih

Hadith #4224 - Sunan Abi Dawud - Abu Barda bin Abi Musa al-Asha'ari أبو بردة / الحارث بن أبي موسى الأشعري; Ali ibn Abi Talib; Asim bin Kulayb bin Shahab عاصم بن كليب بن شهاب بن المجنون; Masdad bin Masrhad مسدد بن مسرهد بن مسربل (Sunan Abi Dawud)
The signet-ring of the Prophet (ﷺ) was of iron polished with silver. Sometimes it remained in my possession. Al-Mu’ayqib was in charge of the signet-ring of the Prophet (ﷺ).
Grade: Hasan

Hadith #4225 - Sunan Abi Dawud - Abdullah bin Hnyn عبد الله بن حنين الهاشمي; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Ali ibn Abi Talib; Ibrahim bin 'Abdullah إبراهيم بن عبد الله بن حنين; Sharayk bin 'Abdullah bin Abi Namr شريك بن عبد الله بن أبي نمر; Sulaiman bin Bilal al-Taymi سليمان بن بلال التيمي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said to me: Say: O Allah, guide me, and set me right. Remember by guidance (hidayah) the showing of the straight path, and remember by setting right (sadad) the setting right of an arrow. Then pointing to the middle finger and the one next to it, he said: He forbade me to wear a signet-ring on this finger of mine or on this (Asim was doubtful). He forbade me to wear qassiyyah (qasi garments) and mitharah. Abu Burdah said: We asked ‘Ali: What is qasiyyah ? He said:
Grade: Sahih

Hadith #4282 - Sunan Abi Dawud - Abu al-Tufayl, 'Amir bin Wathla; al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; al-Qasim bin Abi Bzh القاسم بن أبي بزة; Ali ibn Abi Talib; Uthman bin Muhammad (Sunan Abi Dawud)
The Prophet (ﷺ) said: If only one day of this world remained. Allah would lengthen that day (according to the version of Za’idah), till He raised up in it a man who belongs to me or to my family whose father’s name is the same as my father’s, who will fill the earth with equity and justice as it has been filled with oppression and tyranny (according to the version of Fitr). Sufyan’s version says: The world will not pass away before the Arabs are ruled by a man of my family whose name w
Grade: Hasan Sahih

Hadith #4289 - Sunan Abi Dawud - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; al-Mughira ibn Shu'ba; Ali ibn Abi Talib; Amr bin Abi Qays عمرو بن أبي قيس الرازي الأزرق كوفي; Suh'aib bin Khalid al-Bjly شعيب بن خالد البجلي الرازي (Sunan Abi Dawud)
How will a man who comes against his will (be swallowed up by the earth), Messenger of Allah ? He replied: All will be swallowed up, but each will be raised according to his intention on the Day of Resurrection.
Grade: Sahih

Hadith #4471 - Sunan Abi Dawud - Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; Ali ibn Abi Talib; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي (Sunan Abi Dawud)
He said each time: He should give her the appropriate beating according to Allah’s Book, but not Hurl reproaches at her. He said a fourth time: If she does it again, he should give her the appropriate beating according to Allah’s Book, and then should sell her even if only for a rope of hair.
Grade: Sahih

Hadith #4479 - Sunan Abi Dawud - Abdullah bin Fyrwz عبد الله بن فيروز الداناج; Ali ibn Abi Talib; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Prophet (ﷺ) gave a beating with palm-branches and sandals for drinking wine and Abu Bakr gave lashes. When ‘Umar came to power, he called upon people and said to them: The people are living now near watering placing, and, according to Musaddad’s version, “near villages and watering places, so what do you say about the punishment for (drinking) wine? ‘Abd al-Rahman b. ‘Awf said: We think that you should prescribe the lightest punishment. So he fixed eight lashes for it. Abu Dawud
Grade: Sahih

Hadith #4484 - Sunan Abi Dawud - Ali ibn Abi Talib; Isma'il bin Musa al-Fazari al-Siddi إسماعيل بن موسى الفزاري السدي; Sharayk bin 'Abdullah شريك بن عبد الله النخعي; Umayr bin Sa'id al-Nakha'i عمير بن سعيد النخعي الصهباني; Uthman bin 'Asim bin Husayn عثمان بن عاصم بن حصين أبو حصين (Sunan Abi Dawud)
The Prophet (ﷺ) said: If he is intoxicated, flog him; again if he is intoxicated, flog him; again if he is intoxicated, flog him if he does it again a fourth time, kill him. Abu Dawud said: And there is a similar tradition of Umar ibn AbuSalamah, from his father, on the authority of AbuHurayrah, from the Prophet (ﷺ): If he drinks wine, flog him if he does it so again, a fourth time, kill him. Abu Dawud said: And there is similar tradition of Suhail from Abu Salih on the authority of Abu Hura
Grade: Hasan Sahih

Hadith #4549 - Sunan Abi Dawud - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Ali ibn Abi Talib; Asim bin Dmrh al-Slwly عاصم بن ضمرة السلولي الكوفي; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) addressed on the day of Conquest, or he said: On the conquest of Mecca on the ladder of the House or of the Ka’bah. Abu Dawud said: In a similar way of Ibn ‘Uyainah also transmitted it from ‘Ali b. Zaid, from al-Qasim b. Rab’iah, from Ibn ‘Umar, from the Prophet (ﷺ) ; and Ayyub al-Sukhtiyani transmitted it from al-Qasim b. Rabi’ah from ‘Abd Allah b. ‘Amr like the tradition of Khalid. Hammad b. Salamah also transmitted it from ‘Ali b. Zaid, from Ya
Grade: Da'if

Hadith #4551 - Sunan Abi Dawud - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Ali ibn Abi Talib; Asim bin Dmrh al-Slwly عاصم بن ضمرة السلولي الكوفي; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The bloodwit for unintentional murder which resembles intentional is twenty-five she camels which entered their fourth year, twenty five she-camels which had entered their fifth year, twenty five she-camels which had entered their third year, and twenty five camels which had entered their second year.
Grade: Da'if

Hadith #4761 - Sunan Abi Dawud - Ali ibn Abi Talib; Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Ibn Sirin محمد بن سيرين الأنصاري; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي (Sunan Abi Dawud)
He who disapproves is guiltless, and he who disapproves is safe. Qatadah said : it means one who feels its disapproval in his heart, and one who expresses disapproval in his heart.
Grade: Sahih

Hadith #5060 - Sunan Abi Dawud - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; al-Hakam bin 'Utayba الحكم بن عتيبة; Ali ibn Abi Talib; Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
there is no god but Allah alone Who has no partner, to whom dominion belongs, to whom praise is due, and who has power over everything (omnipotent). Glory be to Allah, and praise be to Allah, and there is no god but Allah, and then he prays: O my Lord, forgive me. Abu Dawud said : Al-Walid’s version has; and he prays, his prayer will be answered. If he gets up, performs ablution, and prays, his prayer will be accepted.
Grade: Sahih

Hadith #5208 - Sunan Abi Dawud - Abdul Malik bin Ibrahim al-Jaddi عبد الملك بن إبراهيم الجدي; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Ali ibn Abi Talib; Sa'id bin Khalid al-Khza'y سعيد بن خالد الخزاعي المدني; Ubaidullah bin Abi Rafi' عبيد الله بن أبي رافع (Sunan Abi Dawud)
The Prophet (ﷺ) said: When one of you comes to an assembly, he should give a salutation and if he feels inclined to get up, he should give a salutation, for the former is not more of a duty than the latter.
Grade: Hasan Sahih